Role of Lymnaea luteola in spreading Schistosoma incognitum in an endemic area - AGRAWAL, M C; GEORGE, JOMINI; GUPTA, SAMIDHA (The Indian Journal of Animal Sciences, 2013)
The potential transmission role of Lymnaea luteola, the snail intermediate host of Schistosoma mcognitum In an endemic area, was studied. Out of 3 991 L. Meola collected [rum Marhai, Suhagi and Gorakhpur areas of Jabalpur, 134 (3.35%) were positive for S. incognitum cercariae with marked seasonal vanation. L. luteola were experimontaily Infected in an artificially prepared tank with pig faeces (60 or 160 g) harbouring S. incognitum miracidia. The snails started shedding S. incognitum cercariae on day 28 or 38 day post-infection (DPI). Cercarlal shedding was the highest on 28 to 43 DPI with the highest infectivity of 26 to 35%. Subsequently, the snails discharging cercariae dimmished to 5-10% with no shedding of cercariae was seen from 58th to 65th DPI reflecting heavy mortality of positive snails within a short Period. The field collected snails (39) were found to discharge S. incognitum cercariae for 1-15 days (average 6 days) till their death. The daily cercarial output per snail varied from 6.6 to 326.6 (minimum) and 106.6-1 006.6 (maximum). Tile total number of S. incognitum cercariae shed by a single snail during its life time ranged from 73 to 4 929 depending on days of survival of the snail.